Strengthening Amidst Turmoil: Resilience as the Key in the Relationship between Organisational Culture, Job Uncertainty, and Employee Agility - Nurmiyati, Nurmiyati; Yuniarsih, Tjutju; Disman, Disman; Sobandi, Ade (Amkop Management Accounting Review (AMAR), 2025)
A volatile and uncertain business environment requires organisations to have employees who are agile in adapting. However, job insecurity can affect employees' psychological conditions and potentially hinder adaptive behaviour. Therefore, resilience is considered important as the ability to survive and thrive amid the pressures of change. This study aims to analyse the influence of organisational culture and job insecurity on employee agility, with employee resilience as a mediating variable. This is a quantitative study using a survey method. The study population consisted of 600 permanent employees in the accessories division of the garment industry in Semarang Regency. The sampling technique used was purposive sampling, with the following criteria: permanent employees with at least 1 year of service, experiencing changes in the work system/environmental pressure, and willingness to participate, resulting in 220 respondents. Data were collected using a Likert scale questionnaire and analysed using the Partial Least Squares approach to Structural Equation Modelling (SEM-PLS). The results showed that organisational culture contributed positively to resilience and employee agility. In this study, job insecurity was also associated with increased resilience and employee agility. Resilience was found to act as a mediator bridging the influence of organisational culture and job insecurity on employee agility. The implications of this study emphasise the importance of strengthening adaptive culture, ensuring clear organisational communication, and developing resilience-building programmes to maintain employee agility in the face of change.